Diabetic nephropathy as an interdisciplinary problem - Wróbel, Marta; Szymborska-Kajanek, Aleksandra; Strojek, Krzysztof (Przewodnik Lekarza/Guide for GPs, 2006)
Introduction of insulin to treatment in diabetic patients reduced mortality caused by hyperglycemic coma. The problem nowadays, resulting from better survival of diabetic patients, is a management of medical and social consequences of late complications. Diabetic nephrotic injury as a result of microangiopathy is one of the most serious late complications. Knowledge of pathophysiology of diabetic nephropathy and proper multifactorial treatment can reduce its consequences.